Pengaruh Kualitas Layanan terhadap Kesetiaan Pengunjung di Desa Wisata - Natalia Kristiani Tandafatu; Yoseph Darius Purnama Rangga (Journal of Management and Bussines (JOMB), 2022)
This study aimed to describe and understand the tangiable, reliability, responsiveness, assurance, and empathy that can affect the loyalty of visitors in Koja Doi Tourism Village. The research method used is a quantitative method. The data used in this study is primary data in the form of questionnaires distributed to tourists visiting the Koja Doi Tourism Village, Sikka Regency. The sample used has a sampling limit of 100 respondents. The results showed, Test result F is known to be a significant value (10.033) with a significant value of 0.00 where smaller 0.05 or below 5%. The results of the T test are known that, a) the significance value of the physical evidence of 0.049 < 0.05; b) the significance value of reliability of 0.048 < 0.05; c) the significance value of the presumption of 0.044 < 0.05; d) the significance value of the guarantee of 0.013 < 0.05; e) the significance value of the attention of 0.036 < 0.05. Conclusions, partially or simultaneously show that physical evidence, reliability, responsiveness, assurance and attention affect the loyalty of visitors.. Keywords: Service Quality, Visitor Loyalty, Koja Doi Tourism Village, Sikka Regency